A Fuller Life - Fuller, Samantha; Goring, Hilton; MacGarvey, Seamus; Purcell, Tyler; Wyn Dunn, Rachel (Carlotta Films, 2018)
Sam Fuller's wonderful life is given the documentary treatment by his daughter, who composes this film of actors reading from Fuller's diaries. Fuller's life spanned almost the entirety of the 20th century, and he remains one of the American cinema's greatest chroniclers of the restless mass of people who inhabit his country ... This documentary gives us a little peek behind the curtain as to why Fuller made the films he did. Boisterous, broiling, bare-knuckle films that looked straight into the madness of the human condition such as "Pickup On South Street", "The Naked Kiss", "Shock Corridor", "The White Dog". It perhaps would've been nice to know a little more about Fuller's films and their making, rather than spend so long detailing his service in the Army during WWII - Fuller demanded to serve in the infantry rather than work on an Army journal - but maybe this documentary's greatest gift is that it leaves you wanting to revisit the mad world of Sam Fuller all over again. [www.eyeforfilm.co.uk]
Keywords: DVD-Video